(Im)mobile languages and literacies in mathematics education - Kate le Roux (Prometeica)
My focus in this conceptual paper is the choice of theoretical concepts and their place-based use analytically for knowledge making about languages and literacies in mathematics education. This is motivated by two related concerns: that the pursuit of certainty, stability, and permanence of meaning of analytic concepts brings some, and not other, existences into being; and that concepts are given meaning in relational, geopolitical place in enfolded pasts, presents, and futures. I write from and for my context in the relational geopolitical South, a context pervaded by questions of what knowledges and practices, for whom, and using what languages and literacies. I propose an imaginary of the world as an archipelago of geopolitical contexts. This is a complex world in which openings and closings, mobilities and permanencies, continuities and discontinuities, entanglements and separations, and incompleteness of languages and literacies and their meanings are the norm, rather than a problem. I argue for a shift in thinking; from the student as language migrant, to flows and fractures in meaning in space and time. For it is in these (im)mobilities that inequities emerge, but also in which the potential for redesign lies. I offer this place-based thinking to prompt conversations about the concepts-in-use in other contexts, towards strengthening knowledge making in mathematics education, without universalising